Characterization of fibroblast‐free CWR‐R1ca castration‐recurrent prostate cancer cell line. Issue 12 (8th June 2016) - Shourideh, Mojgan; DePriest, Adam; Mohler, James L.; Wilson, Elizabeth M.; Koochekpour, Shahriar
Abstract : BACKGROUND: The previously established CWR‐R1 cell line has been used as an in vitro model representing castration‐recurrent prostate cancer. Microscopic observation of subconfluent cells demonstrated two distinct cellular morphologies: polygonal closely aggregated epithelial cells surrounded by bipolar fibroblastic cells with long processes. This study sought to establish and characterize a fibroblast‐free derivative of the CWR‐R1 cell line. METHODS: The CWR‐R1ca cell line was established from CWR‐R1 cells by removing fibroblasts using multiple cycles of short‐term trypsinization, cloning, and pooling single‐cell colonies. Authentication of fibroblast‐free CWR‐R1ca cells was demonstrated by analyzing the expression of cytodifferentiation and prostate‐associated markers, DNA and cytogenetic profiling, and growth pattern in the absence or presence of androgen. RESULTS: CWR‐R1ca is an androgen‐sensitive cell line that expresses the androgen receptor (AR) and its splice variant 7 and the luminal epithelia markers, CK‐8, CK‐18, and c‐Met. CWR‐R1fb fibroblasts isolated from CWR‐R1 cells express AR, hepatocyte growth factor‐α, and mouse β‐actin but not AR‐V7 or epithelial markers. Cytogenetic analysis of CWR‐R1ca cells revealed a hyperdiploid male with numerical gains in chromosomes 1, 7, 8, 10, 11, and 12, deletion of one chromosome 2 allele, structural abnormalities that include der(1)t(1:4), der(4)t(2:4), der(10)t(4:10), and an unbalanced reciprocal translocation between chromosome 6 and 14. DNA‐profiling revealed that CWR‐R1ca cells had significant short‐tandem repeat marker homology with CWR22Pc and CWR22Rv1 cell lines, which indicated lineage derivation from CWR22 prostate cancer xenografts. CWR‐R1ca cells were responsive to the growth stimulatory effects of dihydrotestosterone (DHT) in the femtomolar range. CONCLUSION: This study establishes CWR‐R1ca cells as a fibroblast‐free derivative of the castration‐recurrent CWR‐R1 cell line. Prostate 76:1067–1077, 2016 . © 2016 Wiley Periodicals, Inc.